NIPSNAP protein family emerges as a sensor of mitochondrial health. (14th April 2021) - Fathi, Esmat; Yarbro, Jay M.; Homayouni, Ramin
Abstract: Since their discovery over two decades ago, the molecular and cellular functions of the NIPSNAP family of proteins (NIPSNAPs) have remained elusive until recently. NIPSNAPs interact with a variety of mitochondrial and cytoplasmic proteins. They have been implicated in multiple cellular processes and associated with different physiologic and pathologic conditions, including pain transmission, Parkinson's disease, and cancer. Recent evidence demonstrated a direct role for NIPSNAP1 and NIPSNAP2 proteins in regulation of mitophagy, a process that is critical for cellular health and maintenance. Importantly, NIPSNAPs contain a 110 amino acid domain that is evolutionary conserved from mammals to bacteria. However, the molecular function of the conserved NIPSNAP domain and its potential role in mitophagy have not been explored. It stands to reason that the highly conserved NIPSNAP domain interacts with a substrate that is ubiquitously present across all species and can perhaps act as a sensor for mitochondrial health. Abstract : In response to metabolic stress, NIPSNAP1 and NIPSNAP2 trigger mitophagy via recruitment of PARK1 to remove damaged mitochondria. They may sense the metabolic state of mitochondria via direct interaction with pyruvate dehydrogenase and NADH. Deficits in NIPSNAPs could interfere with mitophagy and result in a variety of pathological conditions.